Causal Factors of Emergence of Multidimensional Poverty Index in Nepal - KC, Nahakul (Research Nepal Journal of Development Studies, 2022)
The study of poverty is a multidimensional phenomenon. Poverty is not an only economic issue but it is social, political, and cultural as well. Who is why and how much poor is a relative concept of the socioeconomic status of the people. To find out the causal factors of the emergence of the multidimensional poverty index, a study has been conducted. It is a qualitative ex-post-facto causal analysis of independent variables of poverty to measure its multidimensional index based on secondary information. It is the study of causal factors to establish MPI in Nepal. The shortage or insufficient amount of independent variables directly causes the impact on Health, Education, and Living Standard of People. Due to the insufficient qualities in Nutrition, Child Mortality, Years of Schooling, School Attendance, Cooking Fuel, Improved Sanitation, Improved Drinking-Water, Electricity, Flooring and Roofing, and Assets Ownership in the human situation of the people of Nepal to address the poverty level the Multidimensional Poverty Index (MPI) was established in Nepal in 2018 officially. The main objective of the study is to determine the causal factors of multidimensional poverty in Nepal. It is absolutely a literature review or content analysis of selected references.